2015
DOI: 10.1093/hmg/ddv468
|View full text |Cite
|
Sign up to set email alerts
|

Modeling structural and functional deficiencies ofRBM20familial dilated cardiomyopathy using human induced pluripotent stem cells

Abstract: Dilated cardiomyopathy (DCM) is a leading cause of heart failure. In families with autosomal-dominant DCM, heterozygous missense mutations were identified in RNA-binding motif protein 20 (RBM20), a spliceosome protein induced during early cardiogenesis. Dermal fibroblasts from two unrelated patients harboring an RBM20 R636S missense mutation were reprogrammed to human induced pluripotent stem cells (hiPSCs) and differentiated to beating cardiomyocytes (CMs). Stage-specific transcriptome profiling identified di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 45 publications
3
87
0
Order By: Relevance
“…Brackets indicate significant differences (P < 0.05) by 1-way ANOVA with Bonferroni's test for multiple comparisons. insight.jci.org https://doi.org/10.1172/jci.insight.94623 disease phenotype after repetitive dosing of norepinephrine (37,38). However, BAG3-mutant lines displayed a positive chronotropic response to stimulation of both α-and β-adrenergic receptors by phenylephrine and isoproterenol, respectively (Supplemental Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Brackets indicate significant differences (P < 0.05) by 1-way ANOVA with Bonferroni's test for multiple comparisons. insight.jci.org https://doi.org/10.1172/jci.insight.94623 disease phenotype after repetitive dosing of norepinephrine (37,38). However, BAG3-mutant lines displayed a positive chronotropic response to stimulation of both α-and β-adrenergic receptors by phenylephrine and isoproterenol, respectively (Supplemental Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro stress testing of hiPSC‐CMs with β‐adrenergic agonist, NE, has led to increased cardiac contractility by the G‐protein coupled second messenger system . Familial DCM has been associated with increased intracellular Ca 2+ overload as well as an increased susceptibility to chronotropic stress from NE . To modulate this Ca 2+ overload and minimize chronotropic stress response, we utilized pretreatment with carvedilol, β‐blocker, and verapamil, L‐type Ca 2+ channel blocker ( Figure a ).…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of normal splicing therefore results in anomalous isoforms of a whole network of cardiac proteins and prevents the heart from effectively responding to both extrinsic and intrinsic stressors . Recent reports have shown that RBM20 familial DCM hiPSC‐CMs have an increased susceptibility to β‐adrenergic stimulation and exhibit stress‐induced phenotypic change in sarcomeric structure …”
mentioning
confidence: 99%
“…iPSC-derived cardiomyocytes with the RBM20 R636S mutation develop a gene expression and splicing profile consistent with cardiomyopathy affecting not only TTN but also the CAMK2D and CACNA1C genes 112 . Sarcomeres within these RBM20 mutant lines were thinner, similar to what was described for TTN mutant iPSC-cardiomyocytes 68 .…”
Section: Dcm Geneticsmentioning
confidence: 96%